A study on culture: system brings to culture standardization in McDonald’s / Noorafiffa Abu Samah - Abu Samah, Noorafiffa (Faculty of Business and Management, 2011)
McDonald’s first come to Malaysia in the year of 1980. McDonald’s corporation USA gave Golden Arches Restaurants Sdn.Bhd the license to operate McDonald’s restaurants in Malaysia. As they are become growth industry, they come with one simple systems as a guide for the workers to do a task. This research paper is the study about how the systems provided by McDonald’s have been creating the new standard culture for this giant firm. From this system there is an impact of the creation of the new standard culture in the McDonald’s. This standard culture can be seen from their way on customer service, the job positioning and the workplace itself. This study was conducted in area of Shah Alam which consists of 80 respondents that choose randomly from the three stores of McDonald’s. From the findings, it was found that the variables have a strong relationship with culture standardization. This research also provided several suggestions that can be improved by McDonald’s to increase the quality of services